2009
DOI: 10.1038/cmi.2009.27
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of TLR9 Expression Affects the Maturation and Function of Murine Bone Marrow-Derived Dendritic Cells Induced by CpG

Abstract: Toll-like receptor 9 (TLR9) is expressed intracellularly by dendritic cells (DCs) and specifically recognizes unmethylated CpG motif. Recognition of TLR9 to CpG DNA can induce DC maturation followed by the subsequent immune responses. Here, RNA interference (RNAi) was used to identify the effect of CpG DNA signaling on DC function. The results showed that transfection of DCs with siRNA specific for TLR9 gene significantly down-regulated TLR9 expression. Immature DCs transfected with TLR9 siRNA did not differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…This finding is consistent with a recent report in which investigators, by using RNA interference, downregulated only partially the expression of TLR9 in dendritic cells. Nevertheless, such downregulation was sufficient to abrogate the effects of CpG ODNs in the induction of dendritic cells maturation (43). In contrast, we observed that all NB-cell lines transfected with siRNA against TLR9 retained the ability to respond to CpG, undergoing apoptosis.…”
Section: Discussioncontrasting
confidence: 40%
“…This finding is consistent with a recent report in which investigators, by using RNA interference, downregulated only partially the expression of TLR9 in dendritic cells. Nevertheless, such downregulation was sufficient to abrogate the effects of CpG ODNs in the induction of dendritic cells maturation (43). In contrast, we observed that all NB-cell lines transfected with siRNA against TLR9 retained the ability to respond to CpG, undergoing apoptosis.…”
Section: Discussioncontrasting
confidence: 40%
“…In human, pDCs express TLR1, 7 and 9, while other DC subsets express all other TLRs but not TLR9 [32]. In the mouse liver, TLR2, TLR4, TLR7 and TLR9 are found on both cDCs and pDCs, but TLR3 is not expressed on pDCs [33,34]. Hepatic cDCs express higher levels of TLR2 and TLR4 than splenic cDCs.…”
Section: Tlr Expression In Hepatic Cell Populationsmentioning
confidence: 95%
“…RNAi has been used to inhibit IRF‐3 expression, which appears to be more attractive due to several distinct advantages with extremely efficient and specific characters . Moreover, this technique is not difficult to perform and its effect can be confirmed within days using simple detection systems, such as real‐time RT‐PCR and Western blot.…”
Section: Discussionmentioning
confidence: 99%